2022
DOI: 10.3389/fpls.2022.1020478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative changes in sugars and lipids show evidence of a critical node for regeneration in safflower seeds during aging

Abstract: During seed aging, there is a critical node (CN) where the population viability drops sharply. Exploring the specific locations of the CN in different species of plants is crucial for understanding the biological storage properties of seeds and refining seed life span management. Safflower, a bulk oil crop that relies on seeds for propagation, has a short seed life. However, at present, its biological characteristics during storage are not clear, especially the changes in metabolic capability and cell structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 98 publications
2
10
0
Order By: Relevance
“…Previous studies have shown that a germination level of 85% is a critical node (CN) for safflower seeds [ 30 ]. In this experiment, we observed that the germination level of C9 seeds was concentrated near the CN, whereas for C15, only approximately half of the seed population survived.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that a germination level of 85% is a critical node (CN) for safflower seeds [ 30 ]. In this experiment, we observed that the germination level of C9 seeds was concentrated near the CN, whereas for C15, only approximately half of the seed population survived.…”
Section: Resultsmentioning
confidence: 99%
“…Seed germination and seedling establishment require energy from compounds stored in the seeds. Effective mobilization is then directly and positively correlated with seed vigor and longevity [ 30 ]. We observed during safflower seed aging the down-regulation of genes involved in the sugar metabolism pathway, including HXK2 , PK , ENO , GAPDH , and others ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raffinose family oligosaccharides are known to contribute to membrane stability under low temperature stress by insertion between lipid headgroups [ 42 ]. Even small concentrations of raffinose have been found to reduce the rate of crystallization of sugars [ 43 ], and thus synthesis of oligosaccharides of the raffinose family may contribute to plant resistance to low temperatures. Average air temperature was found to be inversely correlated with the concentration of myo-inositol (r = −0.97; p = 0.01), galactinol (r = −0.92; p = 0.05), melibiose (r = −0.90; p = 0.06) and raffinose (r = −0.89; p < 0.06) in A. sativa leaves in the cryolithozone area ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%